AI-Enhanced Secure Communication Systems for Next-Generation IoT Networks: Protocols, Threat Mitigation, and Quantum Resilience - M. Rakhshanda*; Sajawal; A. Iqra (Spectrum of Engineering Sciences, 2025)
This research aims to develop a secure communication system enhanced by AI for future IoT networks. It employs advanced security protocols, state-of-the-art threat mitigation techniques, and integrates quantum resilience mechanisms with next-generation IoT secure communication systems. Many of today’s methods used to secure the IoT systems are mostly inherited from legacy systems and often fall short against the kind of attacks we face today (and are likely to face in the future, including quantum attacks). Thus, we took a different approach by using AI and quantum resilience techniques, along with the aforementioned advanced protocols, to secure future IoT systems against not only today’s threats (like DDoS attacks) but also emerging threats (like adversarial attacks on AI models and quantum computing a couple of decades down the road) and to do so in an adaptive and scalable way. The experimental results show that the AI-enhanced intrusion detection system (IDS) is significantly better than conventional IDS. The detection accuracy of the AI-enhanced IDS was determined to be 97.5%. This level of detection meets the criteria of an expert system. Encryption techniques driven by AI cut down on unauthorized access by 40%. For their part, post-quantum encryption methods achieve a 95% success rate in ensuring secure key exchange. AI and PQC algorithms strengthened the already secure IoT networks against threats from quantum computers, guaranteeing their long-term safety. The results indicate that security mechanisms propelled by artificial intelligence do more than just boost the effectiveness of IoT communication. They are also adaptable and scalable responses to the range of new cyber risks that are surfacing today. Moreover, the way we are securing communication for future IoT systems takes full advantage of a very powerful AI framework and hits all the right notes in the IEEE Computational Intelligence Society’s (CIS) vision of an ’AI-powered security framework. Keywords: Artificial Intelligence, communication systems, IoT Networks, Threat Mitigation, Quantum Resilience